2023
DOI: 10.3389/fonc.2022.1092020
|View full text |Cite
|
Sign up to set email alerts
|

Advances in research on the relationship between thymoquinone and pancreatic cancer

Abstract: Pancreatic cancer has one of the worst prognoses among the most common cancers in the world. Its characteristics include a high rate of metastasis and chemotherapeutic resistance, which present major challenges to the medical community. The potential anticancer effects of thymoquinone (TQ), which is the main bioactive compound of the black seeds of the Nigella sativa plant, have recently received widespread attention for their potential use in treating pancreatic cancer. TQ can inhibit cell proliferation, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…[ 26 28 ]. The tumoricidal properties of TQ were recently shown by this research group on breast cancer stem cells by the inhibition of vascularization [ 29 ]. Consistent with our previous study, here we indicated that TQ alone can reduce the orientation of colorectal HT-29 cells toward endothelial lineage.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 28 ]. The tumoricidal properties of TQ were recently shown by this research group on breast cancer stem cells by the inhibition of vascularization [ 29 ]. Consistent with our previous study, here we indicated that TQ alone can reduce the orientation of colorectal HT-29 cells toward endothelial lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies are continuously highlighting the distinguished potential of TQ against pancreatic cancer, where it significantly enhances apoptosis and decreases metastasis through modulating the NF-κB, tumor growth factor-B (TGF-β) and MAPK signaling pathways [137]. Moreover, TQ remarkably increases chemosensitivity in pancreatic cancers resistant to therapy by modulating matrix metalloproteinase enzyme (MMP-1) and NF-κB levels [138]. Table 3 presents updated studies that reported the efficiency of using BCS constituents in various types of cancer.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…Pancreatic cancer is one of the most common cancers worldwide and is characterized by a particularly poor prognosis, high metastatic rates, mortality, and resistance to chemotherapeutic drugs [ 45 ]. It develops as a result of excessive proliferation and DNA mutations in pancreatic cells.…”
Section: Effects Of Nigella Sativa On the Pancreasmentioning
confidence: 99%